Paradise lost : a novel of suspense - Jance, Judith A., 1944- (Avon suspense, 2001)
The desecrated body of a missing Phoenix heiress lies naked, lifeless, and abandoned in the desolate beauty and lonely terror of the high desert night. A hideous crime is inviting death once more into Sheriff Joanna Brady's world. But this time the nightmares of her professional and personal lives are intertwining in ways too awful to contemplate, because one corpse is only the first piece in a twisted and sinister puzzle in which nothing seems to fit. And the next item on a killer's bloody agenda may well be Brady's own beloved daughter.